Analysis of the Role of Information Systems Technology in Lecture Learning during the Corona Virus Pandemic - Muqorobin Muqorobin; Nendy Akbar Rozaq Rais (Institut Teknologi Bisnis AAS Indonesia, 2020)
Abstract— At this time the spread of the Corona Covid-19 Virus was sweeping the world, Indonesia was also affected, especially in the world of education where the teaching and learning process was usually carried out face-to-face in the classroom. So as a result of this pendemi the teaching and learning process must be done online. The role of information systems technology is very meaningful in lecture learning. This study aims to analyze a model of campus learning conditions and the role of information system technology in college learning amid the COVID-19 corona virus pandemic at STMIK Sinar Nusantara Surakarta. The research method is to make observations and literature studies to obtain data and information used in research. The results of this study indicate the use of information technology has a very important role in the implementation of online distance learning in the midst of the corona covid 19 virus pandemic, among online online media such as: google classroom, whatsapp, zoom. Of the online learning media, it is proven that Google Classroom: 55.9% is widely used as media for sharing materials and assignments, while video conferences lectures are the most users of Google Meet as much as: 70.6%. The results of the analysi s of the online learning value are: 44.1%. Based on this data, it shows that the role of information system technology plays an important role and helps in the teaching and learning process amid the Covid-19 corona virus pandemic.